2008
DOI: 10.1158/0008-5472.can-08-0823
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Inflammatory Signalings by Areca Nut Extract and Role ofCyclooxygenase-2−1195G>A Polymorphism Reveal Risk of Oral Cancer

Abstract: Because the mRNA expression of cyclooxygenase-2 (COX-2) is up-regulated by arecoline in human gingival fibroblasts, as shown in our previous study, we further investigated the mRNA expression level of COX-2 and its upstream effectors in three oral epithelial carcinoma cell lines (KB, SAS, and Ca9-22) by using areca nut extract (ANE) and saliva-reacted ANE (sANE). A case-control study of 377 oral squamous cell carcinoma (OSCC) patients and 442 controls was conducted to evaluate the geneenvironment interaction b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…Evidence suggests that COX-2 plays an key role in the carcinogenesis pathway, such as in the inhibition of apoptosis, tumor growth, angiogenesis, invasion and metastasis (Leahy et al, 2000;Tatsuguchi et al, 2004;Wang et al, 2007;Gu et al, 2012;Huang et al, 2013;Saad et al, 2013), which are all crucial to many cancers, especially those belonging to the gastrointestinal tract, such as oral cancer (Chiang et al, 2008), gastric cancer (Liu et al, 2006), esophageal cancer (Kristinsson et al, 2009;Upadhyay et al, 2009), and colorectal cancer (Cox et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that COX-2 plays an key role in the carcinogenesis pathway, such as in the inhibition of apoptosis, tumor growth, angiogenesis, invasion and metastasis (Leahy et al, 2000;Tatsuguchi et al, 2004;Wang et al, 2007;Gu et al, 2012;Huang et al, 2013;Saad et al, 2013), which are all crucial to many cancers, especially those belonging to the gastrointestinal tract, such as oral cancer (Chiang et al, 2008), gastric cancer (Liu et al, 2006), esophageal cancer (Kristinsson et al, 2009;Upadhyay et al, 2009), and colorectal cancer (Cox et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a final total of 38 case-control studies in 37 articles which met our inclusion criteria were identified, including 10814 cases and 16174 controls. Among 38 cases and controls, there were 20 case-controls of Asians (Hamajima et al, 2001;Koh et al, 2004;Liu et al, 2006;Guo et al, 2007;Tan et al, 2007;Chiang et al, 2008;Lin et al, 2008;Saxena et al, 2008;Ueda et al, 2008;Xing et al, 2008;Xu et al, 2008;Tang et al, 2009;Upadhyay et al, 2009;Zhao et al, 2009;Mittal et al, 2010;He et al, 2011;Chang et al, 2012;Li et al, 2012;Shin et al, 2012), 11 of Caucasians (Cox et al, 2004;Pereira et al, 2006;Hou et al, 2007;Moons et al, 2007;Sitarz et al, 2008;Andersen et al, 2009;Hoff et al, 2009;Iglesias et al, 2009;Kristinsson et al, 2009;Pereira et al, 2010;Daraei et al, 2012), 4 of Americans (Ulrich et al, 2005;Gunter et al, 2006;Gong et al, 2009;Thompson et al, 2009), and 1 of Africans (Bye et al, 2011), and 2 of Mixed (Bye et al, 2011;Wang et al, 2012). 9 investigated gastric cancer (Liu ...…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of COX-2 has been reported in human tissues and cell lines as well as in serum of patients with HNC. The increased levels of COX-2 were associated with the risk of tobacco-and betel nutrelated cancers, advance clinical stage, survival and lymph node metastasis (Tang et al, 2003;Molinolo et al, 2007;Chiang et al, 2008;Husvik et al, 2009;Saba et al, 2009;Mittal et al, 2010). In addition, PGE 2 receptors are widely expressed in a variety of HNSCC cell lines as well as in tumor tissues (Abrahao et al, 2010).…”
Section: Cox and Hncmentioning
confidence: 99%
“…Research findings by the International Agency for Research on Cancer have indicated that both tobaccoadded BQ (TA-BQ) and tobacco-free BQ (TF-BQ) are carcinogenic to humans [1,2,8]. Carcinomas of the upper aerodigestive tract are the primary neoplasms associated with their consumption [1,2,[8][9][10][11][12][13][14]. Large-scale epidemiological studies have reported that prolonged TF-BQ use is related to obesity, metabolic syndrome and adverse pregnancy outcomes [15][16][17].…”
Section: Introductionmentioning
confidence: 99%